Hubungan Pengetahuan Ibu Nifas Dengan Pelaksanaan Bounding Attachment Pada Bayi Baru Lahir - Sihotang, Siti Mangaranap Mustika Sari Br; Ginting, Theresia Perbina Br; Ramadhani , Tiara Suci; Hulu, Yudika; Saragih, Elv. Feedia Mona (Journal of Pharmaceutical and Sciences, 2025)
Background: The puerperium is a crucial period after childbirth that lasts for 6 weeks. During this time, the mother's body undergoes physical changes such as the return of the uterus to its original size, the release of lochea, and other hormonal changes. During this postpartum period, the mother can build closer affection. It is the cornerstone of the child's psychological development because of the significance of emotional bonding (bounding attachment) between mother and child. However, a lot of mothers continue to overlook this. Some factors that can influence the implementation of bounding attachment are through good maternal knowledge. Objective: to ascertain how postpartum mothers' understanding and the use of bounding attachment in infants at Pratama Sunggal Clinic relate to one another. Methods: 33 respondents were given questionnaires or had in-person interviews as part of this quantitative study, which uses a cross-sectional design and an analytical survey approach. To determine the link between variables, univariate and bivariate data analysis were employed, along with the chi-square test. Results: The chi-square test revealed a p-value of 0.002 for the association between postpartum moms' knowledge and the application of bounded attachment. Thus, the results indicate that the independent and dependent variables have a substantial association.